2016
DOI: 10.1371/journal.pone.0149642
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Sequencing to Trace Hepatitis A Viruses Circulating in Italy During a Large Multi-Country European Foodborne Outbreak in 2013

Abstract: BackgroundFoodborne Hepatitis A Virus (HAV) outbreaks are being recognized as an emerging public health problem in industrialized countries. In 2013 three foodborne HAV outbreaks occurred in Europe and one in USA. During the largest of the three European outbreaks, most cases occurred in Italy (>1,200 cases as of March 31, 2014). A national Task Force was established at the beginning of the outbreak by the Ministry of Health. Mixed frozen berries were early demonstrated to be the source of infection by the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 14 publications
2
40
0
1
Order By: Relevance
“…NC_001489) of the VP1/2A junction was chosen for genotyping and phylogenetic analysis. This region of HAV was amplified by a nested RT‐PCR reaction as reported . Sequences were obtained by double strand sequencing of the purified PCR products using the GenomeLab DTCS Quick Start Kit and an automated DNA sequencer (Beckman Coulter, Inc., Fullerton, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NC_001489) of the VP1/2A junction was chosen for genotyping and phylogenetic analysis. This region of HAV was amplified by a nested RT‐PCR reaction as reported . Sequences were obtained by double strand sequencing of the purified PCR products using the GenomeLab DTCS Quick Start Kit and an automated DNA sequencer (Beckman Coulter, Inc., Fullerton, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Due to improvements in hygiene and living conditions, Italy is currently considered a country with low/intermediate level of HAV endemicity. The incidence of acute hepatitis A has declined over time in Italy decreasing from 19 cases per 100 000 population in 1997 to 0.6 cases per 100 000 population in 2015 (data from SEIEVA, the Italian integrated epidemiological system for acute viral hepatitis, available at: http://www.iss.it/binary/seie2/cont/Tassi_EpatiteA_2015.pdf), a decline not homogeneous throughout the country mostly because of frequent outbreaks of various origin occurred in some regions . Particularly, in Campania and Apulia (Southern Italy) high annual incidence rates have been reported and several periodic outbreaks have occurred …”
Section: Introductionmentioning
confidence: 99%
“…In the case of environmental samples, amplification of viral nucleic acids by polymerase chain reaction (PCR) assays coupled to reverse transcription (RT-PCR) has been used in water and shellfish. (Vasickova et al, 2005 andBruni et al, 2016). The molecular characterization is as an essential tool to trace HAV outbreaks (Bruni et al, 2016); mixed frozen berries were early demonstrated to be the source of HAV infection by the identity of viral sequences in patients and in food.…”
Section: Discussionmentioning
confidence: 99%
“…(Vasickova et al, 2005 andBruni et al, 2016). The molecular characterization is as an essential tool to trace HAV outbreaks (Bruni et al, 2016); mixed frozen berries were early demonstrated to be the source of HAV infection by the identity of viral sequences in patients and in food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation